Ketzel, the cat who composed - Bates, Amy June (Candlewick Press, 2015)
"Moshe Cotel was a composer who lived in a noisy building on a noisy street in a noisy city. But Moshe didn't mind. Everything he heard was music to his ears. One day, while out for a walk, he heard a small, sad sound that he'd never heard before. It was a tiny kitten! "Come on, little Ketzel," Moshe said, "I will take you home and we will make beautiful music together." And they